Filogenia e evolução de caracteres morfológicos na Ordem Amblypygi Thorell, 1883 (Arachnida) - Navari, Jéssica Lopes Tagliatela (2021)
A new cladistic hypothesis is presented for the first time with 35 species from 19 of the 25 genera, using morphological data. The taxa used included 17 out- and ingroups (Amblypygi). The matrix of morphological characters is based on recent studies focusing on Amblypygi and resulted in 117 characters, eleven of which are exclusive to this work. The characters and their status were encoded in the Mesquite program. Phylogenetic analyzes were performed with equal weights and with implicit weighing in the TNT program, using †Eophrynus Woodward, 1871 as an external group to root the analyses. The discussion is based on the results of the analyses with implicit weighing (k = 5.468750), in order to reduce homoplasies in the preferred tree. The results suggest six synapomorphies for Amblypygi. The new tree generated suggests most families and genera of Amblypygi were not resolved as monophyletic, and those recovered as monophyletic groups had low support, like Euamblypygi, Charontidae and Phrynoidea; except for Amblypygi. The present study highlights the importance of further character exploration and phylogenetic studies in Amblypypi to understand the morphological evolution of the group and to resolve their internal relations.